Strategi Pembinaan Iman PPGT Jemaat Buntu Masakke' Melalui Pemanfaatan Media Digital untuk Memperkuat Pemuda yang Berakar dan Bertumbuh - Ivan Ivan; Rannu Sanderan (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
The digital era has brought profound transformations in religious life, creating both opportunities and challenges for the younger generation of Christians in maintaining their faith. The Toraja Church Youth Fellowship (PPGT) of the Buntu Masakke Congregation is one such community struggling to maintain the steadfastness of its youth's faith amidst the tide of globalization, the temptations of materialism, worldly positions, and the increasingly prevalent dynamics of interfaith romance. This reality drives the need for a faith training strategy that is relevant, contextual, and utilizes the potential of digital technology wisely. This study aims to implement an effective faith training strategy for PPGT through the use of digital media to produce church youth who not only unleash strength in faith, but also grow spiritually and are able to serve in creative and impactful ways in the modern era. This study used a four-month practicum method involving 22 active participants. Three training modules were implemented in stages: (1) Rooted in God's Word in the Digital Age, which encourages the use of Bible applications and digital devotionals; (2) Growing in Christ's Character Amidst Worldly Temptations, which emphasizes the values of integrity, faithfulness, and holiness; and (3) Serving with Creativity and Relevance in the Digital Age, which invites young people to produce digital content with spiritual value. The results of the study showed significant success, with 95% achieving “rootedness,” 80% achieving “growth,” and 86% achieving “serving.” In fact, 63.6% of participants experienced spiritual transformation and are now active as digital ministry drivers. These findings confirm that digital media, when utilized strategically and in harmony with Christian values, can be an effective tool in fostering the faith of the younger generation. Therefore, the church needs to develop a sustainable and contextual digital training model to strengthen the role of young people in current and future ministry.